2002
DOI: 10.1023/a:1015832328023
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This article presents results obtained from studies of the plasticity of changes in social behavior in Drosophila (interactions between individuals in groups) in conditions of homo- and heterogeneous environments. This is the first report of data illustrating self-starting acquisition by female Drosophila of a classical conditioned reflex to contextual factors signaling possible threats from other individuals and blocking the initiation of activity. A previously described operant conditioned reflex also helped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…Learning and memory have been demonstrated in various social contexts in fruit flies as well (6,(8)(9)(10)(11). We have been studying aggression as a behavior indicative of individual fitness in fruit flies and other organisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Learning and memory have been demonstrated in various social contexts in fruit flies as well (6,(8)(9)(10)(11). We have been studying aggression as a behavior indicative of individual fitness in fruit flies and other organisms.…”
mentioning
confidence: 99%
“…Learning in a social context is more complex and likely to involve multiple sensory modalities and elements of both classical and operant conditioning. In one example of socially induced learning and memory, D. melanogaster females in groups become conditioned to low levels of activity and avoid aggressive encounters with other flies (11). This experience leads to a long-lasting behavioral change that can be observed after only 15 min of social exposure.…”
mentioning
confidence: 99%
“…It has been reported that the size of the arena in which the experiment takes places can have a significant influence on the behavior of the flies. Smaller arenas have been described to cause an unconditioned reflex reaction which leads to increased activity or arousal 63 . Furthermore, although these findings have not been analyzed further, an optimal arena size and shape have been proposed to induce aggression between Drosophila males while the lack of possibility for the losing male to escape can enhance aggression 15 , 35 , 63 .…”
Section: Aggression In Drosophilamentioning
confidence: 99%
“…After isolation from a group situation, females restored their level of activity very rapidly showing fast extinction of operant conditioning. However, the classical conditioning in heterogeneous environment was found, when threat from other flies it was associated with context stimuli, and further presentation of context in absence of other flies was sufficient to inhibit activity [8].…”
Section: Introductionmentioning
confidence: 95%
“…Previously, we found that in a group situation, Drosophila melanogaster females showed two unconditioned responses: 1) running from the fly breaking the individual distance, that increased their run frequency, and 2) stopping when continuation of the run threatened collision with another female, that decreased their run duration. By the trial and error method (operant learning) females learn to decrease their locomotor activity that results in reduction of unpleasant contacts with other individuals [8]. After isolation from a group situation, females restored their level of activity very rapidly showing fast extinction of operant conditioning.…”
Section: Introductionmentioning
confidence: 99%